2015
DOI: 10.1016/j.biopsych.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Delta Frequency Optogenetic Stimulation of the Thalamic Nucleus Reuniens Is Sufficient to Produce Working Memory Deficits: Relevance to Schizophrenia

Abstract: Background Low-frequency (delta/theta) oscillations in the thalamocortical system are elevated in schizophrenia during wakefulness and are also induced in the NMDAR hypofunction rat model. To determine whether abnormal delta oscillations might produce functional deficits, we used optogenetic methods in awake rats. We illuminated channelrhodopsin-2 in the thalamic nucleus reuniens (RE) at delta frequency and measured the effect on working memory performance (the RE is involved in working memory (WM), a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 95 publications
(93 reference statements)
2
56
0
Order By: Relevance
“…In addition, GluN2D subunits in the thalamus are likely to contribute to ketamine-induced dysrhythmias. Nucleus reuniens participates in circuits involved in schizophrenia-related symptoms (prefrontal cortex, hippocampus, and ventral tegmentum) (Lisman et al, 2010;Duan et al, 2015;Griffin, 2015;Ito et al, 2015) and is enriched in GluN2D subunits (Watanabe et al, 1993a;Buller et al, 1994). Additionally, inhibition of NMDAR in the reticular nucleus, which contains GluN2D and GluN2C subunits (Watanabe et al, 1993a;Yamasaki et al, 2014), generates telencephalic delta oscillations and potentially schizophrenia-related symptoms ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GluN2D subunits in the thalamus are likely to contribute to ketamine-induced dysrhythmias. Nucleus reuniens participates in circuits involved in schizophrenia-related symptoms (prefrontal cortex, hippocampus, and ventral tegmentum) (Lisman et al, 2010;Duan et al, 2015;Griffin, 2015;Ito et al, 2015) and is enriched in GluN2D subunits (Watanabe et al, 1993a;Buller et al, 1994). Additionally, inhibition of NMDAR in the reticular nucleus, which contains GluN2D and GluN2C subunits (Watanabe et al, 1993a;Yamasaki et al, 2014), generates telencephalic delta oscillations and potentially schizophrenia-related symptoms ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the importance of RE for cognitive processes, such as behavioural flexibility, strategy shifting, inhibitory response control, associative learning, memory consolidation, working memory, fear memory, memory generalization, goal-directed navigation, and executive behaviours (Dollemanvan der Weel et al 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Kincheski et al 2012;Loureiro et al 2012;Cholvin et al 2013;Hallock et al 2013;Prasad et al 2013;Varela et al 2013;Wheeler et al 2013;Xu and Sűdhof 2013;Duan et al 2015;Griffin 2015;Ito et al 2015;Layfield et al 2015;Anderson et al 2015;Prasad et al 2016). This variety of memory-related behaviours has also been associated with the interplay between the medial prefrontal cortex (mPFC) and the hippocampus (Jin and Maren 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, Lisman and colleagues (Duan et al, in press; Lisman et al, 2010; Zhang et al, 2012a,b) provided evidence that RE is a critical component of a complex circuitry which may contribute to schizophrenia—or a circuitry that is central to the glutamate/NMDA receptor (NMDAR) hypofunction model of schizophrenia (Coyle, 1996, 2006; Javitt and Zukin, 1991). More specifically, several symptoms of schizophrenia, notably abnormal delta frequency oscillations in the cortex, are produced by systemic or intrathalamic infusions of NMDA antagonists (Buzsáki, 1991; Zhang et al, 2012a).…”
Section: Re: Electrophysiologymentioning
confidence: 99%
“…The foregoing suggests a vital role for RE in ketamine-induced (or NMDA antagonist-induced) hyperactivity and delta oscillations in HF—two hallmarks of schizophrenia (Boutros et al, 2008; Fehr et al, 2001; Lodge and Grace, 2007, 2011). In a recent report, using optogenetic techniques, Duan et al (in press) showed that driving RE fibers at their termination in the dorsal hippocampus at delta frequencies significantly impaired performance on a WM task. As was convincingly demonstrated, activating RE fibers at delta frequencies (light-on condition) severely altered performance, whereas in the absence of such activation (light-off condition) performance was normal.…”
Section: Re: Electrophysiologymentioning
confidence: 99%